Preparation and creativity help EDs 'beat the heat': parallel processing lessens added burdens. (ED Management, 2005)
Don't wait for a heat wave or dire weather forecasts to start preparing. It will get hot sometime each year.Set up parallel processing systems to handle the addtional influx of heat-injured patients.Train pre-hospital providers to be aware of and report the home circumstances of patients.Pre-stock cooling blankets. If you don't have any, obtain industrial fans from environmental services.